STUDY ON THE PROPAGATION OF Actinidia latifolia AND Actinidia deliciosa IN LAM DONG PROVINCE, VIETNAM - Le Hong En; Hoang Thanh Truong; Nguyen Thanh Nguyen (Tạp chí Khoa học Đại học Đà Lạt)
Actinidia latifolia and Actinidia deliciosa (kiwifruit) are two species with many applications in food and medicine. They are capable of growing and developing in Lam Dong province and similar temperate climates. This study assesses the effect of three plant growth regulators (NAA, IBA, and IAA) on the root formation of Actinidia latifolia cuttings. At the same time, seed germination and the effect of various soil and coir mixtures on the growth of kiwifruit seedlings were tested in the nursery. The results for the Actinidia latifolia cuttings after 60 days showed that NAA and IBA at 1.00% concentration gave the best results, with a rooting percentage of 76.67%, number of roots/cutting of 3.91, and length of roots/cutting of 5.65 cm for NAA. For IBA at 1.00% concentration, the rooting percentage was 66.67%, the number of roots/cutting was 2.43, and the length of roots/cutting was 4.42 cm. When using IAA, the concentration of 1.50% brought the best results, with a rooting percentage of 66.67%, number of roots/cutting of 2.81, and length of roots/cutting of 4.34 cm. The germination percentage of kiwifruit reached 81.00% after 25 days. The best growth of Actinidia deliciosa seedlings was in a media mixture of 25.00% soil and 75.00% coconut coir, with survival percentage, height of seedlings, and number of leaves/seedling of 96.00%, 5.02 cm, and 7.17 leaves, respectively, after 45 days.